Sentencing for the "Crime of Crimes": the evolving "common law" of sentencing of the International Criminal Tribunal for Rwanda - Sloane, Robert D. (Journal of international criminal justice, 2010)
Absent much prescriptive guidance in its Statute or other positive law, the International Criminal Tribunal for Rwanda (ICTR) has been developing, in effect, a common law of sentencing for the most serious international crimes: genocide and crimes against humanity. While it remains, as the Appeals Chamber has said, premature to speak of an emerging penal regime, and the coherence in sentencing practice that this denotes, this comment offers some preliminary reflections on the substantive law and process of sentencing as it has evolved through ICTR practice. Above all, the author argues, sentencing must, but has not yet, become an integral part of international criminal justice rather than, as it has historically been treated, an afterthought. The lack of sufficient attention to sentencing, evident procedurally in the ICTR's abandonment of distinct sentencing hearings and the expedient of transactional sentencing, at times manifests itself in perfunctory sentencing analyses and jurisprudential confusion over the proper role of ostensible sentencing factors including gravity of the offence, zeal, heinous means, prior good character and voluntary commission. Because of the inherent gravity of the crimes, the ICTR's lack of adequate attention to sentencing has not, by and large, led it to impose quantitatively incorrect sentences. But qualitatively, neglect of sentencing inhibits the common law evolution of a mature penal jurisprudence that can contribute to the long-term normative goals of international justice